2021
DOI: 10.1007/s10775-021-09497-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring occupational aspirations of school-age children by fluid intelligence, gender and grade

Abstract: The present study explored the occupational aspirations of school-age children (N = 394) comparing differences by gender, level of intelligence and grade level. Results indicated that girls’ aspirations were more realistic, intrinsically motivated, prosocial and inclusive of higher education than those of boys. Moreover, a higher level of intelligence only from the fourth grade and 10 years of age was associated with higher education aspirations. These results suggest that in choosing occupational aspirations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…School children's gender has been found to be moderately predictive of their career aspirations over various country contexts (Chambers et al, 2018;Nikel, 2021). Large studies involving primary school students from the UK and 19 additional countries (aged 7-11), along with research concerning 22,136 American students aged between 13 and 16, both found average gender-based differences in occupational aspirations for people-centred versus thing-centred jobs (Chambers et al, 2018;Howard et al, 2011).…”
Section: The Influence Of Gender and Parents On Children's Career Asp...mentioning
confidence: 99%
“…School children's gender has been found to be moderately predictive of their career aspirations over various country contexts (Chambers et al, 2018;Nikel, 2021). Large studies involving primary school students from the UK and 19 additional countries (aged 7-11), along with research concerning 22,136 American students aged between 13 and 16, both found average gender-based differences in occupational aspirations for people-centred versus thing-centred jobs (Chambers et al, 2018;Howard et al, 2011).…”
Section: The Influence Of Gender and Parents On Children's Career Asp...mentioning
confidence: 99%
“…For the purpose of this study, a career or occupational aspiration was defined as an "individual's expressed career-related goal(s)" that refers to attaining a specific occupation(s) or a job in a particular occupational field(s) in the future (Rojewski, 2005, p. 132). Career aspirations are considered distinct from career interests in that the former represents an individual's career goal (s) given ideal conditions, whereas the latter refers to an individual's emotional disposition toward certain career options (Nikel, 2021;Rojewski, 2005). A person's career aspiration or goal may result in specific career-related choices over time (e.g., choosing a certain degree programme or job opportunity) (Lent, 2013b).…”
Section: Introduction the Importance Of Children's Career Aspirationsmentioning
confidence: 99%